Beneficial effects of time and energy restriction diets on the development of experimental acute kidney injury in Rat: Bax/Bcl-2 and histopathological evaluation - Alireza Raji-Amirhasani; Mohammad Khaksari; Zahra Soltani; Shadan Saberi; Maryam Iranpour; Fatemeh Darvishzadeh Mahani; Zahra Hajializadeh; Nazanin Sabet (BMC Nephrology, 2023)
Abstract People’s lifestyles and, especially, their eating habits affect their health and the functioning of the organs in their bodies, including the kidneys. One’s diet influences the cells’ responses to stressful conditions such as acute kidney injury (AKI). This study aims to determine the preconditioning effects of four different diets: energy restriction (ER) diet, time restriction (TR) eating, intermittent fasting (IF), and high-fat diet (HF) on histopathological indices of the kidney as well as the molecules involved in apoptosis during AKI. Adult male rats underwent ER, TR, IF, and HF diets for eight weeks. Then, AKI was induced, and renal function indices, histopathological indices, and molecules involved in apoptosis were measured. In animals with AKI, urinary albumin excretion, serum urea, creatinine and, Bax/Bcl-2 ratio increased in the kidney, while renal eGFR decreased. ER and TR diets improved renal parameters and prevented an increase in the Bax/Bcl-2 ratio. The IF diet improved renal parameters but had no effect on the Bax/Bcl-2 ratio. On the other hand, the HF diet worsened renal function and increased the Bax/Bcl-2 ratio. Histopathological examination also showed improved kidney conditions in the ER and TR groups and more damage in the HF group. This study demonstrated that ER and TR diets have renoprotective effects on AKI and possibly cause the resistance of kidney cells to damage by reducing the Bax/Bcl-2 ratio and improving apoptotic conditions.